Arctic Lights Phenomena as an Attraction in Finnish Lapland - Autere, Outi (Lapin ammattikorkeakoulu, 2014)
The primary aim for this research was to examine what arctic lights phenomena are and how they could be seen as an attraction in Finnish Lapland. Furthermore the aim was to find the attraction factors from Finnish Lapland and to examine if the arctic light phenomena could decrease the strong seasonality in tourism business. The thesis was commissioned by The Regional Council of Lapland, which is responsible for the development work of the Lapland region. The methodology used in this research was a qualitative method, including a silent ethnographical approach, data collection as a theoretical background and semi-structured interviews. As the research phenomena were new and held no previous researches, it was vital to understand the concepts and thus a thorough theoretical part was essential. The interviews were conducted with people who had a relevancy to the examined problem through their work. In total there were eight interviews and the interpretation of the results was based on the background information as well as the interviews. The received data showed that nature with its many features is the main attraction in Finnish Lapland. In addition, arctic lights are seen as mystical phenomena, which are seen as defining factors for Lapland. The various stories and myths emphasize the attraction factors and together all these are seen as features which make Finnish Lapland as strong and unique as it is. However, the arctic lights are not seen as a sufficient attraction alone, hence tourism product development is needed. Furthermore the summer products in tourism are seen to have many possibilities. They could be offered to new target groups and to respond the emerging demand of a slower life. In this work the focus was on relevant issues in tourism and the results give a new perspective to the product development approach. Moreover the examined issues can offer a strong base to further research of the topic or they can be utilized in related researches to the Arctic as well. Tämän tutkimuksen ensisijainen ...